Onychophorology, the study of velvet worms, historical trends, landmarks, and researchers from 1826 to 2020 (a literature review) - Monge-Nájera, Julián (2021)
Velvet worms, also known as peripatus or onychophorans, are a phylum of evolutionary importance that has survived all mass extinctions since the Cambrian period. They capture prey with an adhesive net that is formed in a fraction of a second. The first naturalist to formally describe them was Lansdown Guilding (1797-1831), a British priest from the Caribbean island of Saint Vincent. His life is as little known as the history of the field he initiated, Onychophorology. This is the first general history of Onychophorology, which has been divided into half-century periods. The beginning, 1826-1879, was characterized by studies from former students of famous naturalists like Cuvier and von Baer. This generation included Milne-Edwards and Blanchard, and studies were done mostly in France, Britain, and Germany. In the 1880-1929 period, research was concentrated on anatomy, behavior, biogeography, and ecology; and it is in this period when Bouvier published his mammoth monograph. The next half-century, 1930-1979, was important for the discovery of Cambrian species; Vachon’s explanation of how ancient distribution defined the existence of two families; DNA and electron microscopy from Brazil; and primitive attempts at systematics using embryology or isolated anatomical characteristics. Finally, the 1980-2020 period, with research centered in Australia, Brazil, Costa Rica, and Germany, is marked by an evolutionary approach: from body and behavior to geographic distribution; the discovery of how they form their adhesive net; the reconstruction of Cambrian onychophoran communities, the first experimental taphonomy; the first country-wide map of conservation status (in Costa Rica); the first model of why they survive in cities; the discovery of new phenomena like food hiding, parental feeding investment, and ontogenetic diet shift; and the birth of a new research branch, onychophoran ethnobiology. While a few names often appear in the literature, most knowledge was produced by a mass of researchers who entered the field only briefly.